Anesthesiologist‐related factors associated with risk‐adjusted pediatric anesthesia‐related cardiopulmonary arrest: a retrospective two level analysis. Issue 12 (12th August 2021) - Christensen, Robert; Haydar, Bishr; Leis, Aleda; Mentz, Graciela; Reynolds, Paul
Abstract: Background: Pediatric anesthesia‐related cardiac arrest is an uncommon but catastrophic adverse event which has been, in a previous study, associated with anesthesiologist‐related factors such as number of days per year providing pediatric anesthesia. We aimed to replicate this and assess other anesthesiologist‐related risk factors for anesthesia‐related cardiac arrest after adjusting for known underlying risk factors present in the case mix. Methods: We analyzed a large retrospectively collected patient cohort of anesthetics administered from 2006 to 2016 to children at a tertiary pediatric hospital. Three reviewers independently reviewed cardiac arrests and categorized whether they appeared to be related to anesthesia care. Anesthesiologist‐related factors including academic rank, experience, recent case mix, and days per year delivering pediatric anesthesia were assessed for association with anesthesia‐related cardiac arrest after adjustment for underlying case mix. Results: Cardiac arrest occurred in 240 of 109 775 anesthetics (incidence 22/10 000 anesthetics); 82 (7/10 000 anesthetics) were classified as anesthesia‐related. In univariable analyses, anesthesia‐related cardiac arrest was associated with age, (infants ≤180 days, p < .001) American Society of Anesthesiologists Physical Status, (>2, p < .001) American Society of Anesthesiologists Physical Status Emergency, (p = .0035) cardiac surgery, (p < .001) operating room location, (p = .0066) and resident/fellow supervision, (p = .009) but none of the anesthesiologist factors. Even after adjusting for age and American Society of Anesthesiologist Status, none of the anesthesiologist factors were associated with anesthesia‐related cardiac arrest. Conclusions: Case mix explained all associations between higher risk of pediatric anesthesia‐related cardiac arrest and anesthesiologist‐related variables at our institution.